ANALISIS LAPORAN REALISASI ANGGARAN DENGAN MENGGUNAKAN RASIO EFEKTIVITAS DAN RASIO EFISIENSI PADA KANTOR BADAN PERIJINAN TERPADU DAN PENANAMAN MODAL KABUPATEN SERANG - Rukayah Rukayah; Nugrahini Kusumawati; Raden Irna Afriani (Universitas Serang Raya, 2017)
One of the main pillars of a country's economy is the accountability of the stakeholders. In advanced societies of civilization, such accountability is insufficient with oral reports, but should be supported by written accountability reports. Presentation of financial statements is one of written accountability for the financial performance that has been achieved.The aim of this research is how to know financial performance of Badan Perijinan Terpadu dan Penanaman Modal Kabupaten Serang is analyzed from LRA 2014 2016 using effectivity ratio and efficiency ratio.The research method used is descriptive quantitative approach. The results of the research show that average effectiveness ratio from 2014-2016 102% is very effective. This is because the realization of local retribution revenue has increased from year to year. The ratio of efficiency of Badan Perijinan Terpadu dan Penanaman Modal Kabupaten Serangshowed that the average efficiency ratio is 92%,its mean that less efficient. This is because operational expenditure and capital expenditure increase every year. Based on the result of research that financial performance of Badan Perijinan Terpadu dan Penanaman Modal Kabupaten Serang. Keywords : Effectivity Ratio, Efficiency Ratio